Relevansi Penerapan Asas Oportunitas Dalam Sistem Peradilan Pidana Indonesia Dihubungkan Dengan Asas Persamaan Kedudukan Di Hadapan Hukum; The Relevance Implementation of the Opportunity Principle in the Indonesian Criminal Justice System Related to the Equality before the Law Principle - Ramadhan, Kharisma (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Â AbstractIn the Indonesian criminal justice system, dismiss cases based on public interest reason is an embodiment from opportunityÂ  principle as outlined in the provisions of the article 35 letter c Law No. 16 of 2004 concerning the Republic of Indonesiaâs Prosecutor. Application of opportunity principle considered contradictory with the equality before the law principle which has been introduced in the Indonesian Contitution because it creates discrimination in the law enforcement process. Nevertheless, the existence ofÂ  opportunity principle remains recognized in the Indonesian criminal justice system. This article aims to analyze and understand the legislation policy of the opportunity principle, influence of the opportunityÂ  principle to the equality before the law principle as well as the relevance of the opportunityÂ  principle in the Indonesian criminal justice system, based on the provisions of article 35 letter c Law no. 16 of 2004 concerning the Republic of Indonesiaâs ProsecutorAbstrakDalam sistem peradilan pidana Indonesia, pengesampingan perkara demi kepentingan umum merupakan perwujudan dari asas oportunitas yang dituangkan dalam ketentuan pasal 35 huruf c UU No.16 Tahun 2004 Tentang Kejaksaan RI. Penerapan asas oportunitas tersebut dianggap bertentangan dengan asas persamaan kedudukan di hadapan hukum yang telah diintrodusir dalam Konstitusi negara Indonesia karena menimbulkan diskriminasi dalam proses penegakan hukum. Meskipun demikian keberadaan asas oportunitas tetap diakui dalam sistem peradilan pidana Indonesia. Penulisan ini bertujuan untuk menganalisis dan memahami tentang kebijakan legislasi penerapan asas oportunitas, pengaruh penerapan asas oportunitas terhadap asas persamaan kedudukan di hadapan hukum, serta relevansi penerapan asas oportunitas dalam sistem peradilan pidana Indonesia, berdasarkan ketentuan pasal 35 huruf c UU No. 16 Tahun 2004 Tentang Kejaksaan RI.